Genetic Analysis of Cortical Thickness and Fractional Anisotropy of Water Diffusion in the Brain - Kochunov, Peter; Glahn, David; Nichols, Tom; Winkler, Anderson; Hong, Elliott; Holcomb, Henry; Stein, Jason; Thompson, Paul; Curran, Joanne; Carless, Melany; Olvera, Rene; Johnson, MP; et al. (Frontiers in Neuroscience, 2011)
Objectives The thickness of the brain’s cortical gray matter (GM) and the fractional anisotropy (FA) of the cerebral white matter (WM) each follow an inverted U-shape trajectory with age. Both measures are positively correlated, suggesting a common biological mechanism. We employed bivariate genetic analyses to localize quantitative trait loci (QTLs) and individual genes acting pleiotropically upon these phenotypes. Methods Whole-brain and regional GM thickness and FA values were measured from high-resolution anatomical (0.8mm isotropic) and diffusion tensor MR images (1.7x1.7x3.0mm, 55 directions) collected for 712 active participants (274/438 male/females, age=47.9±13.2years) in the Genetics of Brain Structure study. Results Bivariate, whole-genome quantitative trait loci (QTL) analyses of the whole brain measures localized significant (LOD≥3.0) QTLs within chromosome region 15q22-23. More detailed localization was achieved using single nuclear polymorphism (SNP) association and gene expression analyses. No significant association (p<510-5) was observed for 1565 SNPs located within the QTLs. However, post-hoc analysis indicated that 40% of the potentially significant (p≤10-3) polymorphisms were localized to the RORA and NARG2 genes. A potentially significant association (p=310-4) was also observed for the rs2456930 polymorphism that was previously reported as a significant GWAS finding in ADNI subjects. Lymphocyte expression measurements for two genes, located under QTL, RORA and ADAM10 were significantly (p<0.05) correlated with both FA and GM thickness values. Expression measurements for NARG2 was significantly correlated with GM thickness (p<0.05) but failed to show a significant correlation (p=0.09) with FA. Discussion This study identified a novel, significant QTL at 15q22-23. SNP association and correlation with gene-expression analyses indicated that RORA, NARG2 and ADAM10 jointly influence GM thickness and cerebral WM integrity.